Personel jako kryterium doskonalenia kapitału intelektualnego przedsiębiorstwa - Skowron, Paweł (The Staff as a Criterion of Developing Company's Intellectual Capital, 2008)
Development of intellectual capital in companies is indispensable attribute in time when the economy is based on knowledge. Successful improvement of intellectual capital has its source in human capital. Employees are the most important element in company's activity (trading). Investment and assessment of human capital contribute to reach better efficiency of management and create positive relations with others participants of market. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 244-250